- #1

- 8

- 0

## Homework Statement

Convert the following expression into sum of products and products of sums

(AB+C)(B+C'D)

## Homework Equations

Distributive Property

## The Attempt at a Solution

for product of sums it would be (AB+C)(B+C'D) since it is already in this form.

When calculating sum of products I get...

(AB+C)(B+C'D) = ABB+ABC'D+CB+CC'D = ABB+ABC'D+CB+0D = ABB+ABC'D+CB

= A*1+ABC'D+CB = A+ABC'D+CB (this is where I get confused)

=A(1+BC'D)+CB

(I know 1+X=1 but what about 1+BC'D? Can I reduce this further of would A(1+BC'D)+CB be in the correct form?)